Experimental Study on Flow Behavior of Unshrouded Impeller Centrifugal Pumps under Inlet Air Entrainment Condition - Minquan Liao; Qiaorui Si; Meng Fan; Peng Wang; Zhonghai Liu; Shouqi Yuan; Qianglei Cui; Gérard Bois (International Journal of Turbomachinery, Propulsion and Power, 2021)
Results on overall pump head and efficiency performance, pressure pulsation and high speed camera visualization of flow patterns behavior are presented for different inlet air-water void fractions at a given rotational speed. With the increase of inlet void fractions and decrease of the flow rates, the size of bubbles increase and tend to agglomerate in specific impeller passage locations along the blade chord. The starting point of pump breakdown is related to a strong inward reverse flow occurring in a specific location near the shroud gap of the impeller and volute tongue region. Using a constant air void fraction value of 2%, pressure pulsation frequency results are analyzed in relation with local flow mixture patterns and flow rate modification.